Introduction to industrial polyethylene : properties, catalysts, processes - Malpass, Dennis B. (Wiley-Scrivener., 2010)
This concise primer reviews the history of polyethylene and introduces basic features and nomenclatures for this versatile polymer. Catalysts and cocatalysts crucial to the production of polyethylene are discussed in the first few chapters. Latter chapters provide an introduction to the processes used to manufacture polyethylene and discuss matters related to downstream applications of polyethylene such as rheology, additives, environmental issues, etc. Providing industrial chemists and engineers a valuable reference tool that covers fundamental features of polyethylene technology, this new.